Investigating the Variation of Selected Kepler Objects Mid-Transit Times - Çağlar Püsküllü; Oguz Ozturk (Journal of Advanced Research in Natural and Applied Sciences)
We derived minima times from the transit curves of star-planet systems, Kepler-412, Kepler-422, Kepler-427 ve Kepler-435 observed by Kepler space telescope, using the Kwee - van Woerden method and Gauss function fitting. We examined the O-C diagram of each system separately, modelled them with linear and quadratic functions. We obtained that linear models give best fit for O-C distributions. We presented updated light elements of systems and concluded that O-C diagrams of systems can best be represented by the linear model.